"Apparently I've Got Low Self‐Esteem": Schoolgirls' Perspectives On a School‐Based Public Health Intervention. (5th May 2014) - Kvist Lindholm, Sofia; Zetterqvist Nelson, Karin
<x xml:space="preserve">Abstract</x> This article focuses on a psycho‐educational programme, DISA, currently practised in the Swedish schools to prevent girls from developing depressive symptoms. We draw on group interviews with schoolgirls to explore how they describe DISA and how an understanding of the programme is constructed through their arguments. We demonstrate how the girls' version of DISA highlights a contradiction in the intervention that is traceable to the theoretical underpinnings of the programme and the mix of traditions — treatment and prevention — that constitute the intervention. We discuss problematic aspects of DISA and outline implications for policy practice.